Analysis of Public Speaking and Conversation Activities in Improving Students' Verbal Communication Skills at the Darel Azhar Islamic Boarding School Rangkasbitung Lebak - Hunainah; Budi Sudrajat; Faiz Fakhrullah (Formosa Journal of Sustainable Research, 2022)
The formulation in this study is how public speaking activities are at Darel Azhar Islamic Boarding School, how are conversation activities at Darel Azhar Islamic Boarding School, how are students' verbal communication skills at Darel Azhar Islamic Boarding School, and how are public speaking and conversation activities in improving students' verbal communication skills. The purpose of this research is to know public speaking activities at Darel Azhar Islamic Boarding School, to know conversation activities at Darel Azhar Islamic Boarding School, to know the verbal communication skills of students at Darel Azhar Islamic Boarding School and to know public speaking and conversation activities in improving the verbal communication skills of Islamic boarding school students Darel Azhar Rangkasbitung, Lebak. This research was conducted at the Darel Azhar Islamic Boarding School, Rangkasbitung, Lebak, Banten using a descriptive qualitative research method with a field research approach. According to Rijali, a qualitative descriptive method is a type of research that has the objective of describing in a systematic, factual and accurate manner the facts and characteristics of a particular population or in which phenomena are described in detail. Field research (Field Research) is defined as one of the methods used to collect data in qualitative research where in-depth knowledge of the literature is not required. The results of this study indicate that the average level of communication skills of students who have participated in public speaking and conversation activities for a long time is in the fairly good category. This the researchers got from the results of observations, interviews with several teachers who were also mentors for public speaking and conversation activities as well as students who took part in these activities. In addition, observations in the form of tests of students' public speaking abilities are also evidence of the research results.